Analysis of reliability improvement possibilities of thermoelectric cooling devices - Зайков, Владимир Петрович; Мещеряков, Владимир Иванович; Журавлев, Юрий Иванович (Eastern-European Journal of Enterprise Technologies, 2015)
The methods of reliability improvement of single- and multi-stage thermoelectric devices (TED) were considered. It is shown that in the range of modes from the maximum cooling capacity to the minimum failure rate, there are intermediate modes, in which the influence of the parameters of thermoelements (electric conductivity, thermoEMF, efficiency etc.) is different, which suggests that selecting the combinations of parameters allows to improve reliability indicators of the product. The methods of reliability improvement in the design of thermoelectric devices when changing the ratio of height to the cross-sectional area of the thermoelement, which reduces the required number of thermoelements and TED failure rate were analyzed. Within the constructive method, the possibility of choosing the optimal current operating modes of cooling thermoelements for various operating conditions using a criteria-based approach was shown. Possibilities of a parametric method due to: improving the quality of starting thermoelectric materials and enhancing their effectiveness; using various combinations of starting materials at the same efficiency were defined. According to the results of the comparative analysis of the basic reliability parameters and indicators for various combinations of parameters of starting materials, analytical relations for calculating the basic parameters for various operating modes and temperature fluctuations were obtained. It is shown that using the combined method allows to significantly increase the reliability of the device. The above methods of reliability improvement of cascaded TED are a tool in the design of highly reliable thermally loaded equipment using thermoelectric cooling.